Solution of the convective heat transfer problem in a screw coordinate system - Razuvanov, Nikita Georgiyevich (Computational Continuum Mechanics, 2018)
The problems of hydrodynamics and heat transfer in a screw channel flow are considered in a screw coordinate system. In particular, we consider an upward flow of liquid metal in a heated annular channel with a screw edge. The problem is related to the heat exchange in the flow around the fuel cell in the active zone of a nuclear reactor with a liquid-metal coolant. Differential equations of mass, momentum and energy conservation for a liquid metal flow are written in terms of tensor variables for a curvilinear (screw) coordinate system. The well-known equations for the cylindrical system are taken as a basis. They are supplemented with additional terms which arise due the transition to the screw coordinate system. The method of numerical calculation in the helical coordinate system greatly simplifies the description of the geometry and boundary conditions, the construction of the computational grid, the representation and subsequent processing of the results. Numerical simulations of velocity, pressure and temperature fields in a turbulent flow of liquid metal in an annular channel with a screw edge are carried out. Two problems are studied numerically and compared: channels with straight and twisted (screw) edge. Analysis of the results revealed significant influence of the edge twist on the flow and heat transfer characteristics. The presence of a gap between the edge and the outer pipe enhances the twist effects.
Keywords: curvilinear coordinate system; differential equations of continuous media; fluid dynamics; heat transfer; liquid metal